SALIVARY, PLASMA AND CORD BLOOD OXIDATIVE STRESS BIOMARKERS IN MOTHER AND NEONATE: A COMBINED ANALGESIA CONCERN - Shobeiri, Fatemeh; Ranjbar, Akram; Alizadeh, Faegheh Gol; Nazari, Mansour (Journal of Postgraduate Medical Institute, 2017)
Objective: To measure oxidative stress biomarkers in saliva and venous blood of mothers and cord blood of newborns delivered wih and without combined analgesia. Methodology: In this analytical cross-sectional study, carried out in 2015. 68 parturient mothers and newborns were recruited in random to two groups in Fatemieh Teaching Hospital, Hamadan City, Iran. Thirty four of them were delivered via normal vaginal delivery (NVD) and 34 delivered through combined analgesia (CA). This study was designed to measure total antioxidant capacity (TAC), Total thiol molecules (TTM) and catalase activity (CAT), in blood and saliva of mothers at the second stage of labor and cord blood of newborns delivered through these different delivery modes. Results: No significant difference could be observed in the mean of first and third labor stages in CA and NVD groups, but the difference was significant during the second stage in CA and NVD groups, respectively. No statistically significant difference was noticed between the means of oxidative stress parameters (TTM, TAC and CAT) in plasma, saliva and umbilical cord samples in two groups (P> 0.05). A significant positive correlation existed between (plasma and umbilical cord TAC) and (plasma and saliva CAT). There was no significant relationship between newborn birth weight and oxidative stress parameters in two groups. Conclusion: Markers of oxidative stress does not seem to have a major role in the delivery with combined analgesia.